A Proteomic View to Characterize the Effect of Chitosan Nanoparticle to Hepatic Cells: Is Chitosan Nanoparticle an Enhancer of PI3K/AKT1/mTOR Pathway?. (16th March 2014) - Yang, Ming-Hui; Yuan, Shyng-Shiou; Huang, Ying-Fong; Lin, Po-Chiao; Lu, Chi-Yu; Chung, Tze-Wen; Tyan, Yu-Chang
Abstract : Chitosan nanoparticle, a biocompatible material, was used as a potential drug delivery system widely. Our current investigation studies were the bioeffects of the chitosan nanoparticle uptake by liver cells. In this experiment, the characterizations of chitosan nanoparticles were measured by transmission electron microscopy and particle size analyzer. The average size of the chitosan nanoparticle was 224.6 ± 11.2  nm, and the average zeta potential was + 14.08 ± 0.7  mV. Moreover, using proteomic approaches to analyze the differential protein expression patterns resulted from the chitosan nanoparticle uptaken by HepG2 and CCL-13 cells identified several proteins involved in the PI3K/AKT1/mTOR pathway. Our experimental results have demonstrated that the chitosan nanoparticle may involve in the liver cancer cell metastasis and proliferation.